Analisis Penerapan Akuntansi Syariah Berdasarkan Pernyataan Standar Akuntansi Keuangan (PSAK) 102 Tentang Pembiayaan Murabahah Pada Pt. Bank Pembiayaan Rakyat Syariah Metro Madani (BPRS Metro Madani) - Lizza, Irma; Reza, Mohammad Faizal; Mahfudz, Agus (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2023)
In raising funds, Islamic banks accept deposits from the public. At the same time, Islamic banks provide services in the form of financing and investment as well as distributing money. Financing at Islamic banks is one of the pillars of banking. Sharia banks offer several types of financing, including murabahah financing. This study delves into the murabahah financing practices at PT. Metro Madani BPRS, conducted through a qualitative approach examining written and spoken evidence. Murabahah, a key Islamic finance tool, involves the bank purchasing goods upon customer orders and reselling them with a pre-determined profit margin. Unlike conventional banks, PT. Metro Madani avoids speculative inventory purchase. Murabahah goods are valued at their initial sales price and recognized in the financial statements. The murabahah profit margin is initially equal to the purchase price plus the agreed profit. However, at the end of each reporting period, the profit margin is revalued to its net present value, ensuring accurate financial representation. Murabahah receivables are reported at their realized value after adjusting for potential losses, while deferred margins and payments are presented as deductions from their respective receivable and liability accounts. Notably, murabahah liabilities also reflect their realized value, further emphasizing transparency and risk management. This practice adheres to Financial Accounting Standards (PSAK) 102, ensuring accurate and reliable financial reporting of murabahah financing at PT. Metro Madani BPRS.